How to change the world - Flintoff, John-Paul, ....- (London : Macmillan, 2012)
We all want to live in a better world, but sometimes it feels that we lack the ability or influence to make a difference. John-Paul Flintoff offers a powerful reminder that through the generations, society has been transformed by the actions of individuals who understood that if they didn't like something, they could change it. Combining fresh new insights from history, politics and modern culture, this book will give you a sense of what might just be possible, as well as the inspiration and the courage you need to go about improving and changing the world we live in.
Keywords: Maatschappelijke acties